The effectiveness of the case method to improve student learning outcomes in the SMAW subject - Fajrin, M; Purwantono, Purwantono; Irzal, Irzal; Rahim, Bulkia; Zaus, Anggi Agni (Universitas Negeri Padang, 2023)
This study aims to assess the effectiveness of the case method for improving student learning outcomes in the SMAW (Shielded Metal Arc Welding) subject. This research employs classroom action research. The subjects of this study are 11th-grade students majoring in Mechanical Engineering at State Vocational High School 1 Silaut, West Sumatra, Indonesia. Data collection techniques include observation sheets to assess teacher and student activities, tests to evaluate students’ knowledge, and documentation to support the research. The study results indicate that implementing the case method teaching model effectively improves student learning outcomes because students are engaged and interested in learning. This is evident in the learning outcomes in cycle 1, where 64.29% of students achieved passing grades, with nine passing, while 35.71% did not pass, with five students falling short. In cycle 2, student learning outcomes improved to 78.57%, with 11 students passing, while 21.43% did not pass, with three students not meeting the passing criteria. In conclusion, the case method teaching model effectively enhances student learning outcomes in the SMAW subject.